Influence of a province-wide trauma system on motor vehicle collision process of trauma care and mortality: a 10-year follow-up evaluation - Tallon, John M., MD, MSc; Fell, Deshayne B., MSc; Karim, Saleema A., MHSA, MBA; Ackroyd-Stolarz, Stacy, PhD; Petrie, David, MD (Canadian Journal of Surgery, 2012)
Background Mature trauma systems have evolved to respond to major injury-related morbidity and mortality. Studies of mature trauma systems have demonstrated improved survival, especially among seriously injured patients. From 1995 to 1998, a province-wide trauma system was implemented in the province of Nova Scotia. We measured the proportion of admissions to a tertiary level trauma centre and the proportion of in-hospital deaths among patients with major injuries as a result of a motor vehicle collisions (MVCs) before and 10 years after provincial trauma systems implementation. Methods We identified major trauma patients aged 16 years and older using external cause of injury codes pertaining to MVCs from population-based hospital claims and vital statistics data. Individuals who were admitted to hospital or died because of an MVC in 1993–1994 (preimplementation), were compared with those who were admitted to hospital or died in 2003–2005 (postimplementation). Results Postimplementation, there was a 9% increase in the number of seriously injured individuals with primary admission to tertiary care. This increase was statistically significant even after we adjusted for age, head injury and municipality of residence (relative risk [RR] 1.09, 95% confidence interval [CI] 1.04–1.14). The probability of dying while in hospital in the postimplementation period decreased by 29% (adjusted RR 0.57, 95% CI 0.32–1.03), although this difference was not statistically significant. Conclusion Individuals seriously injured in MVCs in Nova Scotia were more likely to be admitted to tertiary care after the implementation of a province-wide trauma system. There was a trend toward decreased mortality, but further research is warranted to confirm the survival benefit and delineate other contributing factors.